Peran DPRKP Cipta Karya Prov. Jatim dalam Penyelenggaraan Program Prasarana Sarana Utilitas Umum (PSU) - Ica Veronika Kartiko; Singgih Manggalou (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to find out what is the role of the DPRKP Cipta Karya Prov. East Java in organizing the Infrastructure, Facilities, and Public Utilities (PSU) Program. PSU is one of the messenger programs of the Ministry of Public Works and Public Housing (PUPR) in terms of development assistance in the form of providing components of housing infrastructure, facilities, and utilities to improve decent housing for low-income people. The research method that the author uses is Descriptive Qualitative Method guided by the four tasks of the Housing and Settlement Area Sector in accordance with Governor Regulation No. 84 of 2019, especially article number 9, namely Formulation, Implementation, Coordination, and Control or supervision. Through data collection techniques with observation and interviews, it was found that the role of the DPRKP Cipta Karya Prov. Jatim in the field of housing and residential areas has carried out its duties in implementation, coordination, and control or supervision. However, in policy formulation, the role of the DPRKP Cipta Karya Prov. East Java Housing and Settlement Division has not taken a role because it is still guided by central regulations, namely Permen-PUPR No. 7 of 2022.